Large-scale pathways-based association study in amyotrophic lateral sclerosis. - Kasperaviciute, D; Weale, M; Shianna, K; Banks, G; Simpson, C; Hansen, V; Turner, M; Shaw, C; Al-Chalabi, A; Pall, H; Goodall, E; Morrison, K; et al. (2007)
Sporadic amyotrophic lateral sclerosis (ALS), a devastating neurodegenerative disease, most likely results from complex genetic and environmental interactions. Although a number of association studies have been performed in an effort to find genetic components of sporadic ALS, most of them resulted in inconsistent findings due to a small number of genes investigated in relatively small sample sizes, while the replication of results was rarely attempted. Defects in retrograde axonal transport, vesicle trafficking and xenobiotic metabolism have been implicated in neurodegeneration and motor neuron death both in human disease and animal models. To assess the role of common genetic variation in these pathways in susceptibility to sporadic ALS, we performed a pathway-based candidate gene case-control association study with replication. Furthermore, we determined reliability of whole genome amplified DNA in a large-scale association study. In the first stage of the study, 1277 putative functional and tagging SNPs in 134 genes spanning 8.7 Mb were genotyped in 822 British sporadic ALS patients and 872 controls using whole genome amplified DNA. To detect variants with modest effect size and discriminate among false positive findings 19 SNPs showing a trend of association in the initial screen were genotyped in a replication sample of 580 German sporadic ALS patients and 361 controls. We did not detect strong evidence of association with any of the genes investigated in the discovery sample (lowest uncorrected P-value 0.00037, lowest permutation corrected P-value 0.353). None of the suggestive associations was replicated in a second sample, further excluding variants with moderate effect size. We conclude that common variation in the investigated pathways is unlikely to have a major effect on susceptibility to sporadic ALS. The genotyping efficiency was only slightly decreased ( approximately 1%) and genotyping quality was not affected using whole genome amplified DNA. It is reliable for large scale genotyping studies of diseases such as ALS, where DNA sample collections are limited because of low disease prevalence and short survival time.